Social Mapping for Human Resource Development Planning in Desa Losari Sumowono District, Semarang Regency - Imam Anas Hadi (Prosperity: Journal of Society and Empowerment, 2021)
This research aims to discover a social map in Losari Village, Sumowono District, Semarang Regency and to find out the use of social mapping for human resource development planning in Losari Village, Sumowono District Semarang Regency. This research uses descriptive qualitative research to describe the research object and uses observation, interviews, and documentation techniques to obtain data. The researcher used the Miles and Huberman technique regarding the data analysis, namely data reduction, data presentation, and drawing conclusions and verification. The mapping results know social problems, including socio-cultural, economic, and infrastructure problems. Then it can uncover the natural and human potential in Losari village, the potential of human resources in the form of farmers, and improve education in Losari Village. No less important are actors who play a role in social relations. Mapping benefits can be obtained first, the actual area of a village, the geographical location of the village and the boundaries of the area, and the village's history. Both the conditions and characteristics of the community, the potential and problems that exist in the village emerged. The third is social mapping to develop or create programs according to the potential and problems that exist in the region.